Summary of the British Thoracic Society guideline for diagnostic flexible bronchoscopy in adults. Issue 8 (9th July 2013) - Du Rand, I A; Blaikley, J; Booton, R; Chaudhuri, N; Gupta, V; Khalid, S; Mandal, S; Martin, J; Mills, J; Navani, N; Rahman, N M; Wrightson, J M; et al.
Abstract : Flexible bronchoscopy is an essential, established and expanding tool in respiratory medicine. Its practice, however, needs to be safe, effective and for the right indications to maximise clinical utility. This guideline is based on the best available evidence and is a revised update of the British Thoracic Society guideline on diagnostic flexible bronchoscopy.